Grenada : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association (World Bank, Washington, DC, 2018)
This report provides a Debt Sustainability Analysis (LIC-DSA) of Grenada’s public and publicly guaranteed (PPG) external and total debt for 2018. The macro-framework incorporates all previous debt restructurings, including the November 2017 haircut on commercial debt. Total public debt has declined from 108 percent of GDP in 2013 to below 71 percent of GDP in 2017 with external public debt declining to 48 percent of GDP. This reduction was made possible through a comprehensive restructuring of Grenada’s public debt, fiscal consolidation, and robust economic growth. Nevertheless, with some US$15.7 million (1.4 percent of GDP) in unresolved arrears to official bilateral creditors, Grenada’s external debt risk rating remains ‘in debt distress’. Going forward full regularization of arrears and continued fiscal discipline will be needed to keep the debt on a downward path and withstand the existing vulnerabilities to external shocks and natural disasters.